Insight into Reepithelialization: How Do Mesenchymal Stem Cells Perform? - Deyun Chen; Haojie Hao; Xiaobing Fu; Weidong Han (Stem Cells International)
Wound reepithelialization is a cooperative multifactorial process dominated by keratinocyte migration, proliferation, and differentiation that restores the intact epidermal barrier to prevent infection and excessive moisture loss. However, in wounds that exhibit impaired wound healing, such as chronic nonhealing wounds or hypertrophic scars, the reepithelialization process has failed. Thus, it is necessary to explore a suitable way to mitigate these abnormalities to promote reepithelialization and achieve wound healing. Mesenchymal stem cells (MSCs) have the capacity for self-renewal as well as potential multipotency. These cells play important roles in many biological processes, including anti-inflammation, cell migration, proliferation, and differentiation, and signal pathway activation or inhibition. The mechanism of the involvement of MSCs in reepithelialization is still not fully understood. An abundance of evidence has shown that MSCs participate in reepithelialization by inhibiting excessive inflammatory responses, secreting important factors, differentiating into multiple skin cell types, and recruiting other host cells. This review describes the evidence for the roles that MSCs appear to play in the reepithelialization process.